Dynamics of flatter wind pump installation - Крижановський, А. С. (Proceedings of National Aviation University (archive), 1999)
Wind pump installation is considered, in which as quality wind engine is used flatter wind engine with vertically located wing blade. For research of dynamics of installation its mathematical model is constructed. Determined is the law of movement of wing blade at a connected load and main characteristics of wind pump installation